Unveiling The Negative Impact Of Social Media Addiction On Family Relationships - Hamdi Bacha, Yasmine (University of Eloued جامعة الوادي, 2023)
Abstract: This research paper delves into the detrimental impact of social media addiction on family relationships. With the increasing prevalence of social media in society, concerns have arisen about its effects on family bonds. The study explores how excessive social media use affects communication dynamics quality time spent together, emotional connection, privacy, and fulfillment of familial responsibilities. The findings emphasize the challenges faced by families and offer recommendations for addressing and mitigating the negative effects of social media addiction. By fostering open communication, setting boundaries, prioritizing quality time, promoting emotional connection, and seeking professional help when needed, families can strike a healthier balance between online and offline interactions, thus strengthening their relationships in the face of social media addiction.
Keywords: Social Media; Social Media Addiction; Family Relationships; Communication; Negative impact